The US-EU security relationship the tensions between a European and a global agenda - Rees, G. Wyn 1963- (European Union series (Palgrave Macmillan (Firm), 2011)
Contemporary security challenges such as the rise of international terrorism and the threat from 'states of concern' have - in recent years - forced the US and the EU to adapt their relationship and work together in new ways